Leveraging Remote-Sensing Data to Assess Garage Door Damage and Associated Roof Damage - Kovar, Rachel N.; Brown-Giammanco, Tanya M.; Lombardo, Franklin T. (Frontiers in Built Environment, 2018)
Garage doors or roll-up doors on residential and commercial structures are vulnerable components that are often damaged in windstorms. Failures of these large openings can lead to internal pressurization, which can cause additional structural damage to roofs and walls. This study utilized high spatial resolution oblique remote-sensing data to assess the condition of garage doors and roof structure damage on residential structures following two tornadoes and one hurricane. The performance of the garage doors was evaluated to determine performance trends based on the size of the door and orientation to the wind, as well as estimated wind speed. The study found higher failure rates of garage doors in the hurricane event than the tornadoes, but roof structural damage was more common following a garage door failure in a tornado. Additionally, roof structural damage was uncommon for buildings where the garage door remaining intact, regardless of event type.